News and Views into the SNARE Complexity in Arabidopsis - Kim, Sang-Jin; Brandizzi, Federica (Frontiers in Plant Science, 2012)
Secretory organelles are engaged in a continuous flux of membranes, which is believed to occur mostly via transport vesicles. Being critical in maintaining several cellular functions, transport vesicles are membrane-enclosed sacs that temporarily store and then deliver membrane lipids, protein and polysaccharides. SNAREs have a crucial role in vesicle traffic by driving membrane fusion and conferring fidelity through the formation of specific SNARE complexes. Additionally, specific roles of SNAREs in growth and development implicate that they are versatile components for the life of a plant. Here, we summarize the recent progress on the understanding of the role of SNAREs and highlight some of the questions that are still unsolved.